2017
DOI: 10.3389/fnins.2017.00444
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Long-Term Plasticity of Cerebellar Purkinje Cells Eliminates the Effect of Anodal Direct Current Stimulation on Vestibulo-Ocular Reflex Habituation

Abstract: Anodal direct current stimulation (DCS) of the cerebellum facilitates adaptation tasks, but the mechanism underlying this effect is poorly understood. We have evaluated whether the effects of DCS effects depend on plasticity of cerebellar Purkinje cells (PCs). Here, we have successfully developed a mouse model of cerebellar DCS, allowing us to present the first demonstration of cerebellar DCS driven behavioral changes in rodents. We have utilized a simple gain down vestibulo-ocular reflex (VOR) adaptation para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Since anodal tDCS induces long-term potentiation (LTP)-like plasticity, and improved learning, the results provide further evidence against the long-standing view that long-term depression (LTD) at the parallel fiber-Purkinje cell synapse is the only and the essential kind of plasticity underlying learning in the cerebellar cortex [233]. In accordance, a recent study in mice found that anodal tDCS effects depend on LTP and the intrinsic plasticity of Purkinje cells in VOR habituation [234]. This has been further supported in recent years by Johansson et al (2015) and Gutierres-Castellanos et al (2017) [235, 236].…”
Section: Non-invasive Stimulation In Humanssupporting
confidence: 53%
“…Since anodal tDCS induces long-term potentiation (LTP)-like plasticity, and improved learning, the results provide further evidence against the long-standing view that long-term depression (LTD) at the parallel fiber-Purkinje cell synapse is the only and the essential kind of plasticity underlying learning in the cerebellar cortex [233]. In accordance, a recent study in mice found that anodal tDCS effects depend on LTP and the intrinsic plasticity of Purkinje cells in VOR habituation [234]. This has been further supported in recent years by Johansson et al (2015) and Gutierres-Castellanos et al (2017) [235, 236].…”
Section: Non-invasive Stimulation In Humanssupporting
confidence: 53%
“…The stimulation in the cerebellar vermis, in reaching the prefrontal cortex, likely coursed through the fastigial nucleus and then to the thalamus (Bostan et al, 2013; Lisberger and Thach, 2013). Stimulation of Purkinje cells, in the outermost layer of the cerebellum, leads to changes in the cerebellar output, which in turn modulates the output of deep cerebellar nuclei (DCN) (Oulad Ben Taib and Manto, 2013, 2016; Das et al, 2017). Because inputs from Purkinje cells to the DCN are inhibitory, increased activation of Purkinje cells with high frequency stimulation (Maeda et al, 2000b; Hallett, 2007) inhibits the tonic activity of the DCN.…”
Section: Discussionmentioning
confidence: 99%
“…Although tACS and tDCS modulate cerebellar plasticity and functional connectivity, these electric techniques most likely operate in a different way than the transcranial magnetic stimulation (TMS) techniques such as cTBS [10]. Obviously, more will be learned from animal models [15].…”
Section: Introductionmentioning
confidence: 99%